2017
DOI: 10.1371/journal.pone.0181198
|View full text |Cite
|
Sign up to set email alerts
|

Sexual diversity in the United States: Results from a nationally representative probability sample of adult women and men

Abstract: In 2015, we conducted a cross-sectional, Internet-based, U.S. nationally representative probability survey of 2,021 adults (975 men, 1,046 women) focused on a broad range of sexual behaviors. Individuals invited to participate were from the GfK KnowledgePanel®. The survey was titled the 2015 Sexual Exploration in America Study and survey completion took about 12 to 15 minutes. The survey was confidential and the researchers never had access to respondents’ identifiers. Respondents reported on demographic items… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
92
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(103 citation statements)
references
References 29 publications
11
92
0
Order By: Relevance
“…Most of the participants reported having other types of sexual intercourses in addition to vaginal, similar to the sexual behavior of the adult population in the United States. [ 31 ] One in 10 man reported same-sex intercourse, which is higher than frequencies reported in previous studies done in Brazil, [ 32 ] but similar to the proportion reported by other Latin American countries. [ 22 ] The differences with previous study could be due to the increasing proportion of men who engage in same-sex relationships [ 33 ] or due to differences in the sample population.…”
Section: Discussionsupporting
confidence: 73%
“…Most of the participants reported having other types of sexual intercourses in addition to vaginal, similar to the sexual behavior of the adult population in the United States. [ 31 ] One in 10 man reported same-sex intercourse, which is higher than frequencies reported in previous studies done in Brazil, [ 32 ] but similar to the proportion reported by other Latin American countries. [ 22 ] The differences with previous study could be due to the increasing proportion of men who engage in same-sex relationships [ 33 ] or due to differences in the sample population.…”
Section: Discussionsupporting
confidence: 73%
“…However, despite that diversity, only one-half of the women reported preferring vaginal penetration, supporting the idea than men place a higher value on vaginal penetration as a sexual activity. 27…”
Section: Masturbation Styles and Preferencesmentioning
confidence: 99%
“…Individuals in consensually nonmonogamous (CNM) relationships, however, remain notably underserved by researchers and practitioners. Yet these individuals are also sexual minorities (Herbenick et al, 2017) and stand to benefit from informed study and care. Like LGBT communities, CNM communities face social stigma in regard to their personal identities and relationships (Moors, Matsick, Ziegler, Rubin, & Conley, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing two US Census-based quota samples to explore the prevalence of CNM experiences, Haupert, Gesselman, Moors, Fisher, and Garcia (2016) found that more than 20% of single adults in the U.S. reported prior experiences with CNM relationships. Using a probability sample of U.S. adults, Herbenick et al (2017) found that 1.6% of those in relationships described their partnerships as “open”.…”
Section: Introductionmentioning
confidence: 99%